Development of Groundstro Forehand Aids for Field Tennis Games - Hartanto, Dwi; Arifin, Zainal (Jurnal Ilmiah Mandala Education (JIME), 2023)
Coaching for the sport of field tennis includes various aspects involving players, coaches and the infrastructure needed to develop abilities and skills in the sport of field tennis. The aim of this research is to develop a Forehand groundstroke tool for playing tennis. This research uses an Assist ball tool made using iron to develop forehand groundstrokes for beginners. This research study used 9 experts divided into several expert fields, 3 material experts in the field of sports, 3 experts in the field of equipment or media and 3 in the field of trainers, in testing the equipment using small groups involving 6 experts in their respective fields, 2 material experts with 87% participation, 2 trainer experts 88% and 2 produk experts 86%. The research method used is research and development, research and development activities which aim to develop and create a new technological product or process end in the end seeing the ball fall can be said to be accurate. It is hoped that this research can help the world of field tennis in Indonesia so that it can trigger the emergence of new ideas or concepts in technological tools in the future.